Bitter silence allows sexual harassment to continue in workplace: A qualitative study in Iranian nurses - Zeighami, Maryam; Zakeri, Mohammad Ali; Mangolian Shahrbabaki, Parvin; Dehghan, Mahlagha (Frontiers in Public Health, 2022)
Background Sexual harassment in the workplace is continuing. However, the rate of sexual harassment disclosure is low, which causes many problems. Non-disclosure of sexual harassment can cause nurses' psychological distress and physical harm, and affect their productivity and quality of care. Therefore, the present study aimed to investigate the reasons why Iranian nurses stayed silent and did not disclose sexual harassment in their workplace. Method This qualitative descriptive-explorative study was conducted to investigate the reasons why Iranian nurses (n = 18) stayed silent on sexual harassment. Conventional content analysis and purposeful sampling method were used in this study. Data was collected through in-depth semi-structured interviews. Maximum variance in terms of age, sex, work experience, education level, marital status, and type of hospital and ward was considered in order to obtain rich information. Guba and Lincoln criteria were used to increase the study's trustworthiness, while the Graneheim and Lundman approach was used to analyze the content. Results The research data indicated 112 codes, a major category, 4 subcategories, and 9 primary categories. The major category, “The missing link is bitter silence; sexual harassment is still going on,” includes four subcategories: fear of social stigmas, organizational and legal barriers, family barriers, and personal barriers. Conclusions Nurses cannot break their silence on sexual harassment because they are afraid that disclosure of sexual harassment has negative consequences for their personal and professional lives. Policies and strategies should be developed to encourage nurses to disclose sexual harassment. This issue must be studied socially, culturally, and politically.